Engineering procurement construction in the context of belt and road infrastructure projects in West Asia: A SWOT analysis - Mohammad Ajmal Nikjow; Li Liang; Xijing Qi; Samad Sepasgozar (Journal of Risk and Financial Management, 2021)
Engineering procurement and construction (EPC) is a normative practice globally approved since China has been engaging in international cooperation under the Belt and Road Initiative (BRI) infrastructure development. EPC has been adopted in the delivery of BRI infrastructure projects in other countries. Compared to the domestic method of contract, EPC remains at a low level in management practice, such as a lack of coordinating diverse project stakeholders, high cost of information communication, and risk in complex environments in West Asia (WA). However, no research has conducted a strategic analysis of the current situation of EPC for BRI infrastructure projects in West Asian countries. This study aims to understand the current status quo of EPC for BRI projects in WA by performing a strength, weakness, opportunity, and threats (SWOT) analysis and with the support of data collected from the literature review and semi-structured interviews with EPC stakeholders. The study brings awareness along which internally and externally circumstances of the EPC for BRI infrastructure projects can be perceived by major stakeholders participating. The four critical strategies presented based on the SWOTs identified could help EPC firms develop and promote EPC to implement BRI infrastructure projects in WA at the strategic level.
Keywords: 330; Belt and Road Initiatives; engineering procurement construction; infrastructure; SWOT analysis; West Asia